Limb heaviness as a sensorimotor disorder alters rehabilitation adherence after a stroke - Chen, Yuanyuan; Yang, Hongyan; Chen, Yanqin; Wei, Hui; Lan, Meijuan (Frontiers in Neurology, 2022)
Introduction: To the best of our knowledge, how perceived limb heaviness affects rehabilitation adherence is still unknown. Since rehabilitation adherence is very important to the people’ function recovery with stroke, it is important to explore the relationship between perceived limb heaviness and rehabilitation adherence. Methods: We retrospectively reviewed the data of consecutive people with stroke recruited in the CIRCLE study. The influence of age, gender, time from onset to enrollment, education background, hypertension, diabetes, Modified Rankin scale(MRS), and National Institutes of Health Stroke Scale (NIHSS) on rehabilitation adherence were analyzed. Multiple linear regression analysis was used to examine the association between perceived limb heaviness and rehabilitation adherence changes. Results: A total of 108 participants completed the study. 40(37.0%) participants felt limb heaviness. The mean scores of Medical Research Council (MRC) scale for the upper affected limbs strength was 3.05±1.7 and the mean score of the exercise adherence questionnaire(EAQ) was 34.27 ± 8.9. Univariate analysis showed that rehabilitation adherence level had differ in muscle strength of the upper limbs and whether had perceived limb heaviness. After adjusting for independent predictors, we found perceived limb heaviness to be associated with rehabilitation adherence (B=-9.681±1.494, P<0.05), The R2 was 0.332 if the muscle strength of the upper limb and perceived limb heaviness in the model, whereas the R2 was 0.074 if the model was without perceived limb heaviness. Conclusion: By identifying the people with stroke with limb heaviness, such that it led to lower levels of motor functional rehabilitation adherence. We must pay more attention to limb heaviness, give effective intervention to improve rehabilitation adherence and promote patient recovery.